2021
DOI: 10.5114/aoms/136447
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID-19 Another Case of Obesity Paradox? - Results from An International Ecological Study on behalf of the REPROGRAM Consortium Obesity Study Group

Abstract: IntroductionObesity has emerged as one of the major risk factors of severe morbidity and cause-specific mortality among severe acute respiratory syndromes coronavirus-2 (SARS-CoV-2) infected individuals. Patients with obesity also have overlapping cardiovascular diseases and diabetes, which make them increasingly vulnerable. This novel ecological study examines the impact of obesity and/or body mass index (BMI) on rates of population-adjusted cases and deaths due to coronavirus diseases 2019 (COVID-19).Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In the study by Bhaskar et al [ 34 ], the authors showed that BMI is an independent predictor of cause-specific COVID-19 mortality, and not of the caseload per million population. Countries with obesity rates of 20–30% had a significantly higher number of deaths per million population than both those in <20% and >30% slabs.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Bhaskar et al [ 34 ], the authors showed that BMI is an independent predictor of cause-specific COVID-19 mortality, and not of the caseload per million population. Countries with obesity rates of 20–30% had a significantly higher number of deaths per million population than both those in <20% and >30% slabs.…”
Section: Discussionmentioning
confidence: 99%
“…2 More specifically, health comorbidities may predispose patients to an increased risk of poor outcomes following COVID-19 infection. [2][3][4] Previous studies have indicated a relatively higher prevalence of diabetes in COVID-19 patients compared to those without diabetes. 5 Moreover, previous meta-analyses have indicated that diabetes is associated with increased risk of severe COVID-19, acute respiratory distress syndrome (ARDS), and in-hospital mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with poor outcomes, including in‐hospital morbidity and mortality, in COVID‐19 hospitalized patients are of considerable interest 2 . More specifically, health comorbidities may predispose patients to an increased risk of poor outcomes following COVID‐19 infection 2‐4 . Previous studies have indicated a relatively higher prevalence of diabetes in COVID‐19 patients compared to those without diabetes 5 .…”
Section: Introductionmentioning
confidence: 99%